2010
DOI: 10.1111/j.1365-2605.2009.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Phantom testis syndrome: prevalence, phenomenology and putative mechanisms

Abstract: Chronic phantom pain has been found in up to 78% of limb amputees and is a major complication of limb amputation. Less is known about phantom phenomena after the amputation of other, i.e. visceral, parts of the body. In a retrospective design, we identified 539 patients in whom one testis was removed between 1995 and 2005. The operative technique was a unilateral standard radical inguinal orchiectomy. The underlying pathology in all cases was a testicular germ cell tumour. All patients received a detailed ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…The questionnaire method itself may favor symptomatic patients, who are more likely to respond than asymptomatic patients, resulting in an overestimation of chronic pain and sexual dysfunction after testicular cancer treatment. With a view to similar results in a previous study (Sörös et al, 2003; Pühse et al, 2010) we are confident that the reported prevalence is not influenced by major selection bias. The best way to assess whether presurgical and postsurgical pain is confounding the patients' reporting is to carry out the survey at several time points before and after surgery and regularly during follow‐up.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The questionnaire method itself may favor symptomatic patients, who are more likely to respond than asymptomatic patients, resulting in an overestimation of chronic pain and sexual dysfunction after testicular cancer treatment. With a view to similar results in a previous study (Sörös et al, 2003; Pühse et al, 2010) we are confident that the reported prevalence is not influenced by major selection bias. The best way to assess whether presurgical and postsurgical pain is confounding the patients' reporting is to carry out the survey at several time points before and after surgery and regularly during follow‐up.…”
Section: Discussionsupporting
confidence: 89%
“…The testis has rich visceral and somatosensory innervations, predisposing it for the development of pain and phantom sensations. Although the exact mechanisms of pain and phantom sensations after testicular amputation are unknown, we assume that plastic changes in the cortex with the loss of physiologic inhibition and hyperexcitability of the stump of the nerves are involved in the development of painful sensations after removal of the testis (Pühse et al, 2010). From neurophysiologic sight, an implanted testicular prothesis may interfere in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, phantom sensations have also been reported after mastectomy (Staps et al, 1985;Björkman et al, 2008), testis resection (Pühse et al, 2010), teeth extraction (Marbach, 1978), eye enucleation (Sörös et al, 2003), and even surgical removal of internal organs (Dorpat, 1971;Arcadi, 1977;Ovesen et al, 1991).…”
Section: Functional Reorganization Related To Nonpainful Phantom Phenmentioning
confidence: 99%
“…Puhse et al [14] published on 539 postorchidectomy patients operated on between 1995 and 2005. Out of 238 respondents, 53% reported a phantom experience, with a prevalence of phantom testis pain of 25%, nonpainful phantom sensations 16% and male gonad hallucinations 12%.…”
Section: Surgerymentioning
confidence: 99%